ความต้องการใช้สารสนเทศการเกษตรของเกษตรกรตำบลหนองบัว อำเภอโกสุมพิสัย จังหวัดมหาสารคาม (Needs of Agricultural Information among Farmers in Nong Bua Sub-district, Kosumpisai District, Mahasarakham Province) - เวชโอสถศักดา, ฉันทนา (บรรณศาสตร์ มศว, 2019)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาความต้องการใช้สารสนเทศการเกษตรของเกษตรกร ตำบลหนองบัว อำเภอโกสุมพิสัย จังหวัดมหาสารคาม กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ เกษตรกรทั่วไปจาก 3 หมู่ ได้แก่ บ้านหนองผือ หมู่ 1 และหมู่ 10 และบ้านกอก หมู่ 2 จำนวน 156 ครัวเรือน กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ เกษตรกรทั่วไป ครัวเรือนละ 1 คน จำนวน 156 คน โดยการกำหนดขนาดกลุ่มตัวอย่างโดยใช้เกณฑ์ ร้อยละ30 เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ผลการวิจัยพบว่า เกษตรกรร้อยละ 69.3 เป็นเพศหญิง ส่วนใหญ่จบการศึกษาระดับประถมศึกษา เกษตรกรส่วนใหญ่ต้องการใช้สารสนเทศการเกษตรที่เกี่ยวกับโรคและศัตรูพืช/สัตว์ แหล่งสารสนเทศการการเกษตรที่ใช้ คือ ศูนย์การเรียนรู้ชุมชน และสอบถามจากผู้นำชุมชน ซึ่งได้แก่ ผู้ใหญ่บ้านและกำนัน เกษตกรมีความต้องการใช้สารสนเทศทางการเกษตรจากสื่อ/กิจกรรมทางการเกษตรในรายการโทรทัศน์ Abstract The purpose of this study was to study the needs of using agricultural information in Nong Bua Sub district, Kosum Phisai District, Mahasarakham Province. The population and samples in this study is the farmers who live in Ban Phue No. 1 and 10 and Ban Kok No. 2 in Nong Bua Sub district, Kosum Phisai District, Mahasarakham Province. These were 156 farmers by using 30 % rate in simple random sampling method. The data were collected by questionnaries. Using descriptive statistics, the researcher analyzed the data collected in term of percentage. The findings of this study were as follows: 69.3 % of the farmers were female. Most of them were educated at primary level. The information they used were regarding pests, weed, and disease control. The investigation of information sources revealed that in term of people, most of farmers got required by consulting village leaders. The investigation of information sources revealed that in term of places, most of the farmers need to use the community learning center. In terms type of media, the farmers mostly got information from television.